The Influence of Brand Trust and Service Quality on Customer Satisfaction at The Shalimar Boutique Hotel Malang - Allisa Ana Mawardah; Asminah Rachmi; Achmad Zaini (Manajemen Bisnis, 2025)
This study analyzes the effect of brand trust and service quality on customer satisfaction at The Shalimar Boutique Hotel Malang. The hotel industry faces intense competition, requiring management to consistently maintain customer satisfaction. This quantitative research involved 100 respondents who had stayed at the hotel at least twice, selected through purposive sampling. Data were collected using questionnaires and analyzed with multiple linear regression, supported by validity, reliability, and classical assumption tests. The results show that brand trust has a significant positive effect on customer satisfaction. Service quality also has a significant positive influence on customer satisfaction. Simultaneously, brand trust and service quality together significantly affect customer satisfaction. These findings confirm that both variables are crucial determinants of guest satisfaction. The implication is that The Shalimar Boutique Hotel needs to strengthen brand trust through reliability, honesty, and security while maintaining high-quality services through tangibles, reliability, responsiveness, assurance, and empathy. Enhancing these aspects not only increases satisfaction but also strengthens customer loyalty and the hotel’s competitive advantage.